‘They Get It, They’ve Been Through It’: How Lived Experience Can Shape Understandings of Peer Parent Advocacy - Harriet Lloyd; Cerys Harris; Leanne Cook; Jennifer Williams; Layla Roderick; Zoe Price; Clive Diaz (Social Sciences)
Parent advocacy is increasingly being adopted as a means of encouraging parents to understand and engage with child protection professionals. Current research suggests that it is highly valued by parents and professionals alike, but the focus of data collected thus far has largely been on services that have been received, which may make positive assessments more likely. As part of an ongoing project evaluating parent advocacy services across England, researchers consulted a public involvement group consisting of parents with experience of child protection services. The group provided a set of considerations for designing advocacy services by reflecting on the forms of support they would have liked to receive. This represented a subtle but important change in the balance of power, which means that their considerations differed in some ways from what our research participants had said. The group’s participation prompted researchers to adapt their developing logic model and to consider how the data collection might have excluded some important perspectives.